The Progression of Mycosis Fungoides During Treatment with Mogamulizumab: A BIO-MUSE Case Study of the Tumor and Immune Response in Peripheral Blood and Tissue - Angelica Johansson; Eirini Kalliara; Emma Belfrage; Teodor Alling; Paul Theodor Pyl; Anna Sandström Gerdtsson; Urban Gullberg; Anna Porwit; Kristina Drott; Sara Ek (Biomedicines)
Background/objectives: Mycosis fungoides (MF) is a rare malignancy, with an indolent course in the early stages of the disease. However, due to major molecular and clinical heterogeneity, patients at an advanced stage of the disease have variable responses to treatment and considerably reduced life expectancy. Today, there is a lack of specific markers for the progression from early to advanced stages of the disease. To address these challenges, the non-interventional BIO-MUSE trial was initiated. Here, we report on a case study involving one patient, where combined omics analysis of tissue and blood was used to reveal the unique molecular features associated with the progression of the disease. Methods: We applied 10× genomics-based single-cell RNA sequencing to CD3+ peripheral T-cells, combined with T-cell receptor sequencing, to samples collected at multiple timepoints during the progression of the disease. In addition, GeoMx-based digital spatial profiling of T-helper (CD3+/CD8−), T-cytotoxic (CD3+/CD8+), and CD163+ cells was performed on skin biopsies. Results. The results pinpoint targets, such as transforming growth factor β1, as some of the mechanisms underlying disease progression, which may have the potential to improve patient prognostication and the development of precision medicine efforts. Conclusions: We propose that in patients with MF, the evolution of the malignant clone and the associated immune response need to be studied jointly to define relevant strategies for intervention.